2013
DOI: 10.1371/journal.pone.0071592
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Fish Oil and Genistein, Individually or in Combination, Protects Bone against the Adverse Effects of Methotrexate Chemotherapy in Rats

Abstract: Cancer chemotherapy has been shown to induce long-term skeletal side effects such as osteoporosis and fractures; however, there are no preventative treatments. This study investigated the damaging effects of anti-metabolite methotrexate (MTX) subcutaneous injections (0.75 mg/kg BW) for five days and the potential protective benefits of daily oral gavage of fish oil at 0.5 mL/100 g BW (containing 375 mg of n-3 PUFA/100 g BW), genistein (2 mg/100 g BW), or their combination in young adult rats. MTX treatment alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 72 publications
6
40
0
Order By: Relevance
“…Reiner and Bertha described this phenomenon as if the trabeculae were formed of small islands of bone [35] . Also, MTX therapy might lead to overall reduction of trabecular bone volume [36] . Experimental studies of MTX induced bone defects revealed that apart from the reduced osteoblast number and trabecular bone volume; there was a significant increase in marrow adiposity [31,37] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reiner and Bertha described this phenomenon as if the trabeculae were formed of small islands of bone [35] . Also, MTX therapy might lead to overall reduction of trabecular bone volume [36] . Experimental studies of MTX induced bone defects revealed that apart from the reduced osteoblast number and trabecular bone volume; there was a significant increase in marrow adiposity [31,37] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to increased usage of anti-cancer drugs and their significant effect on skeletal health, it becomes important to explore potential supplementary treatments that may be useful in protecting bone during cancer chemotherapy [14] . Folinic acid, soy products rich in isoflavone, genistein, and fish oils rich in omega-3 polyunsaturated fatty acids were previously used to improve bone health [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Following fixation, cells were stained in Nile Red to identify adipogenic colonies under fluorescence microscope (excitation, 485 nm; emission, 525 nm). Adipogenic differentiation potential was expressed as the percentage of positive colonies over the total toluidine blue-stained colonies as described [22].…”
Section: Ex Vivo Mineralisation Assay and Adipogenic Assaymentioning
confidence: 99%
“…Both DNA and non-DNA damages exert on epithelial and submucosal cells following chemotherapy, which cause intricate sequential biological events, such as generation of reactive oxygen species (ROS), transcription factor activation, pro-inflammatory cytokine expression/accumulation, nitrosative stress, cell apoptosis, reduction in epithelial cell proliferation, changes in growth factor expression, proteolysis, bacterial colonization, and activation of enteric immune and nervous systems (Al-Dasooqi et al, 2013;Kolli et al, 2008;Logan et al, 2007;2009;Qutob et al, 2013;Sonis, 2009;Xian et al, 1999Xian et al, , 2000Xian et al, , 2002Xian, 2003;Zhan et al, 2014). Great efforts have been applied to evaluate/ develop interventions that prevent or reduce the toxic effects of chemotherapy, such as intensive oral hygiene care and usage of antiseptics, antimicrobial and anti-inflammatory agents, cytokines, growth factors, antioxidants, immune modulators and homeopathic agents (McCulloch et al, 2014;Nadhanan et al, 2013;Qutob et al, 2013;Rodríguez-Caballero et al, 2012).…”
Section: Introductionmentioning
confidence: 99%